FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris pada SKPD di Kabupaten Lombok Tengah) - Ikang Murapi (InFestasi, 2016)
This study was conducted to determine the factors that affect the informatioan quality of localgovernment financial reports. Collecting data this study used a questionnaire survey. The data collectedis then processed using SPSS version 17.0. The statistical method used to test the hypothesis is multiplelinear regression analysis. Results of hypothesis testing is the implementation of the Regional FinancialAccounting System, Utilization of Information Technology and Internal Control System The governmenthas a positive and significant impact on Information Quality of Local Government Financial Statements,but do not be influenced by the Human Resource Competency.